Pengaruh Penggunaan Singkong Sebagai Bahan Pakan Sumber Karbohidrat Terhadap Pertambahan Bobot Badan Sapi Potong : Literatur Review - Arfah Maulani Ashari; Anisa Ramadhani; Muthia Fayza Lubis; Muhammad Azril Rizky Ramadhan; Putra Julianto Nugraha; Ulfa Nurrofingah; Ainun Nafisah (Zoologi: Jurnal Ilmu Peternakan, Ilmu Perikanan, Ilmu Kedokteran Hewan, 2026)
This study aims to analyze the effect of using cassava (Manihot esculenta crantz) as a carbohydrate-based feed ingredient on body weight gain in beef cattle. The review was conducted using a descriptive literature study approach based on sixteen scientific articles discussing the nutritional composition, processing methods, and performance responses of beef cattle fed cassava-based diets. The analysis shows that cassava contains 17.45–88.6% dry matter, 2.4–21.45% crude protein, and 11.35–92.2% nitrogen-free extract, with variations influenced by plant part, processing method, and hydrocyanic acid (HCN) content. Processing techniques such as fermentation and ensiling can reduce HCN levels by more than 70% while increasing crude protein content up to 25%, thereby improving digestibility and feed efficiency. The inclusion of cassava in the form of flour, dried chips, pulp, or fermented peel consistently enhances dry matter intake and average daily gain (ADG) of beef cattle at inclusion levels of 20–50% in the diet. Overall, cassava has strong potential as a locally available, economical, and sustainable feed ingredient to improve beef cattle productivity.